Hepatic expansion of a virus-specific regulatory CD8(+) T cell population in chronic hepatitis C virus infection - Accapezzato, Daniele (American Society for Clinical Investigation, 2004)
Regulatory T (T(R)) cells consist of phenotypically and functionally distinct CD4(+) and CD8(+) T cell subsets engaged both in maintaining self-tolerance and in preventing anti–non-self effector responses (microbial, tumor, transplant, and so on) that may be harmful to the host. Here we propose that the proinflammatory function of virus-specific memory effector CCR7(–)CD8(+) T cells, which are massively recruited in the liver, are inefficient (in terms of IFN-γ production) in patients with chronic hepatitis C virus (HCV) infection because of the concomitant presence of virus-specific CCR7(–)CD8(+) T(R) cells producing considerable amounts of IL-10. These CD8(+) T(R) cells are antigen specific, as they can be stimulated by HCV epitopes and suppress T cell responses that are in turn restored by the addition of neutralizing anti–IL-10. This study provides for the first time to our knowledge direct evidence of the existence of virus-specific CD8(+) T(R) cells that infiltrate the livers of patients with chronic HCV infection, identifies IL-10 as a soluble inhibitory factor mediating suppression, and suggests that these cells play a pivotal role in controlling hepatic effector CD8(+) T cell responses.